Driving Impulse Buying: The Role of Product Assortment, Store Atmosphere, and Hedonic Shopping Motivation among Retail Customers in Malang City - Deka, Rio Era; Ilyas, Taufiq Rahman (PINISI Discretion Review, 2025)
This study aims to analyze the influence of product assortment, store atmosphere, and hedonic shopping motivation on impulse buying behavior among retail customers in Malang City. The research employed a quantitative method using an explanatory research approach. Data were collected through questionnaires distributed to 100 respondents using a purposive sampling technique. Multiple linear regression analysis was conducted to examine the effect of the independent variables on the dependent variable.The findings indicate that product assortment, store atmosphere, and hedonic shopping motivation, both individually and simultaneously, have a positive and significant influence on impulse buying behavior. The store atmosphere variable demonstrates the most dominant effect in encouraging customers to engage in impulse buying, followed by product assortment and hedonic shopping motivation. This study contributes to retail business practitioners by providing insights for designing effective marketing strategies, emphasizing the importance of creating engaging shopping experiences to enhance consumers’ impulsive purchasing behavior.